2016
DOI: 10.1177/1759091416670492
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of Interferon Beta Attenuates Neuronal Apoptosis via the JAK1/STAT3/BCL-2 Pathway in a Rat Model of Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: Neonatal hypoxic-ischemic encephalopathy (HIE) is an injury that often leads to detrimental neurological deficits. Currently, there are no established therapies for HIE and it is critical to develop treatments that provide protection after HIE. The objective of this study was to investigate the ability of interferon beta (IFNβ) to provide neuroprotection and reduce apoptosis after HIE. Postnatal Day 10 rat pups were subjected to unilateral carotid artery ligation followed by 2.5 hr of exposure to hypoxia (8% O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Besides, evidences also showed that ERK1/2 and JAK/STAT3 pathways participated in pro-angiogenesis after stroke [39,40]. JAK1/ STAT3 pathway was reported to participate in neuronal apoptosis in a rat model of neuronal hypoxic-ischemic encephalopathy [41]. Our results went in line with these earlier investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, evidences also showed that ERK1/2 and JAK/STAT3 pathways participated in pro-angiogenesis after stroke [39,40]. JAK1/ STAT3 pathway was reported to participate in neuronal apoptosis in a rat model of neuronal hypoxic-ischemic encephalopathy [41]. Our results went in line with these earlier investigations.…”
Section: Discussionsupporting
confidence: 91%
“…The sections were imaged by microscope (Olympus-BX51). Brain tissue loss and ventricular dilation were measured and calculated with ImageJ 4.0 (Media Cybernetics) (Ballabh, 2010; Dixon et al, 2016). Calculations were performed in a blinded fashion.…”
Section: Methodsmentioning
confidence: 99%
“…Fluoro-Jade C staining was used to detect degenerating neurons in the brain (Dixon et al, 2016). Briefly, brain sections were rinsed in basic alcohol consisting of 1% sodium hydroxide in 80% ethanol, 70% ethanol, distilled water, 0.06% potassium permanganate, 0.0001% solution of Fluoro-Jade C (Histo-chem) dissolved in 0.1% acetic acid vehicle, distilled water and xylene.…”
Section: Methodsmentioning
confidence: 99%